Internal Control Capabilities with Menyama Braya Concept as An Effort To Saving Bad Loans in Bumdes - Ni Luh De Erik Trisnawati; Ni Made Rianita; Riana Dewi Kartika (International Journal of Social Science and Business, 2020)
Bad credit must still be saved to reduce the amount of losses and keep BUMDes afloat. The purpose of this research is to analyze the internal control capabilities with local wisdom of menyama braya as a bad loans saving effort. The research population is all bumdes active in Buleleng Regency. The sampling in this study used random sampling techniques so that 92 observational data were obtained. The data analysis technique used in this study is sem component based analysis method, Partial Least Square (PLS). Based on the results of the coefficient path, the influence of the internal control system on the bad credit saving strategy is significant which is shown with a value of T statistics of “1.96” which is 2,890 or p-values is significant < 0.05. Cultural Moderation between the relationship of the internal control system to the bad credit saving strategy shows a static T value of 2,637 greater than 1.96 with a p-values value of <0.05). The results showed that internal control systems had a positive effect on bad loans saving strategies. And the culture of menyama braya moderates the relationship between internal control systems and bad credit saving strategies. BUMDes who are obedient in their internal control system, then based on acting using the concept of menyama braya culture, turned out to be an effective force in the efforts to save bad loans that occurred.